Dy3+-, Tb3+-, and Eu3+-activated NaCa4(BO3)3 phosphors for lighting based on near ultraviolet light emitting diodes. (March 2018) - Shi, Meiling; Zhu, Chaofeng; Wei, Mingzhi; He, Zhigang; Lu, Meng
Abstract: A variety of Dy 3+ -, Tb 3+ - and Eu 3+ -singly or doubly or triply activated NaCa4 (BO3 )3 phosphors for light emitting diodes applications were synthesized via a high temperature solid state reaction technique under an ambient atmosphere. These phosphors were studied by X-ray diffraction, scanning electron microscopy, photoluminescence excitation and emission spectra, Commission International de I'Eclairage chromaticity coordinates, and correlated color temperatures. The emission colors of Dy 3+ -, Tb 3+ -, and Eu 3+ -doped phosphors can be successfully tuned from green to yellow and then to white by appropriately changing the Tb 3+ content and the excitation wavelengths. The correlated color temperatures can also be tailored from cold color to warm color. Furthermore, the energy transfer process from Dy 3+ to Tb 3+ in the Dy 3+ /Tb 3+ codoped phosphors exists, which is discussed based on the luminescence spectra and energy level diagram analysis. The NaCa4 (BO3 )3 :Dy 3+, Tb 3+, Eu 3+ phosphors reported here demonstrate promising applications in the fields of near ultraviolet based light emitting diodes. Highlights: Dy 3+ /Tb 3+ /Eu 3+ doped NaCa4 (BO3 )3 phosphors for LEDs are studied. Tunable luminescence of the as-prepared phosphors is realized. The energy transfer from Dy 3+ to Tb 3+ in the Dy 3+ /Tb 3+ codoped phosphors occurs.